1991
DOI: 10.1111/j.1432-1033.1991.tb16394.x
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of a monomeric insulin

Abstract: The solution conformation of des-(B26-B30)-insulin (DPI) has been investigated by 'H-NMR spectroscopy. A set of 250 approximate interproton distance restraints, derived from two-dimensional nuclear Overhauser enhancement spectra, were used as the basis of a structure determination using distance geometry (DG) and distance-bound driven dynamics (DDD). Sixteen DG structures were optimized using energy minimization (EM) and submitted to short 5-ps restrained molecular dynamics (RMD) simulations. A further refinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The A-chain N-terminal region is non-helical and imprecisely defined. Motional narrowing in analysis of slowly exchanging amide resonances in 2 H 2 O (Kline & Justice, 1990;Knetgel et al, 1991;Jo rgensen et al, 1992;Hua et al, 1993a,b;Ludvigsen et al, 1994); protection is observed in each case in the B-chain a-helix and C-terminal A-chain helix. DKP-[A6-A11] Ser exhibits novel non-native features.…”
Section: Solution Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The A-chain N-terminal region is non-helical and imprecisely defined. Motional narrowing in analysis of slowly exchanging amide resonances in 2 H 2 O (Kline & Justice, 1990;Knetgel et al, 1991;Jo rgensen et al, 1992;Hua et al, 1993a,b;Ludvigsen et al, 1994); protection is observed in each case in the B-chain a-helix and C-terminal A-chain helix. DKP-[A6-A11] Ser exhibits novel non-native features.…”
Section: Solution Structuresmentioning
confidence: 99%
“…This view is supported by three additional observations. First, of native elements of secondary structure, only the A1-A8 a-helix fails to exhibit protection of amide protons from exchange (Kline & Justice, 1990;Hua et al, 1991Knetgel et al, 1991;Jo rgensen et al, 1992;Ludvigsen et al, 1994). Second, among crystal structures the A1-A8 helix is least regular in geometry and most readily deformed by lattice packing (Badger, 1992).…”
Section: Competing Evolutionary Constraints?mentioning
confidence: 99%
“…The B-chain secondary structure in the native insulin consists of an N-terminal region of variable conformation (residues B1-B8), a central a-helix between two disulfide bridges (B9-B19), a [3-turn (B20-B23) and a C-terminal [3-strand (B24-B28) [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several groups have published NMR study results, carried out at low pH using modified insulins or co-solvents, in an effort to counteract its selfassociation behavior [12][13][14][15][16]. This study has been carried out by 2D-1H-NMR and CD spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…The functional surface of insulin has long been the object of speculation Pullen et al, 1976; Despite many years of investigation by mutagenesis (Katsoyannis et al, 1973;Cosmatos and Katsoyannis, 1975;Danho et al, 1975;Inouye et al, 1978;Tager et al, 1979;Inouye et al, 1981;Kobayashi et al, 1982;Okada et al, 1981;Shoelson et al, 1983;Kitagawa et al, 1984;Kobayashi et al, 1986;Nakagawa and Tager, 1986;Nanjo et al, 1986;Nakagawa and Tager, 1987;Casaretto et al, 1987;Mirmira and Tager, 1989;Wang et al, 1991;Mirmira and Tager, 1991;Nakagawa and Tager, 1992;Hu et al, 1993;Kaarsholm et al, 1993;Weiss et al, 2000), nuclear magnetic resonance (NMR) 1 spectroscopy (Hua and Weiss, 1990;Knegtel et al, 1991;Hua et al, 1992;Sørensen and Led, 1994;Hua et al, 1995;Jørgensen et al, 1996;Hua et al, 1996;Olsen et al, 1996;Ludvigsen et al, 1998;Olsen et al, 1998;Kurapkat et al, 1999) 103 and X-ray crystallography Peking Insulin Structure Group, 1971;Bi et al, 1984;Liang et al, 1985;Dai et al, 1987;Badger et al, 1991;Derewenda et al, 1991...…”
Section: Introductionmentioning
confidence: 99%